The guest room [compact disc, unabridged] : a novel - Bohjalian, Chris, 1962- (Books on Tape ; Random House Audio, 2016)
When Kristin Chapman agrees to let her husband, Richard, host a bachelor party, she expects a certain amount of debauchery. She brings their young daughter to Manhattan for the evening, leaving her Westchester home to the men and their hired entertainment. What she does not expect is this: bacchanalian drunkenness, her husband sharing a dangerously intimate moment in the guest room, and two women stabbing and killing their Russian bodyguards before driving off into the night.